Public Policy Making in the Western Balkans: Case Studies of Selected Economic and Social Policy Reforms - Thomas, Margo (Springer, 2015)
Developing and ‘transition’ economies face myriad challenges in their attempts to achieve and maintain political stability and foster the economic growth essential for national security, the social well-being of current citizens and sustainable environments for future generations. Governments in the Western Balkans have striven to achieve all of the above, and this volume assesses the nature of their experiences as well as the level of their success in doing so. Featuring detailed case studies of public policy reforms in the region as well as comparative analysis on a range of indicators, the book analyzes the role of key players in setting the political agenda as well as implementing policy reforms. It also distils the lessons that can be learned from the Western Balkan experience, recommending strategies for enhancing the policy making process. In addition, it examines the developmental role played by the full spectrum of policy actors, including the private sector, NGOs, special interest groupings, international financial institutions, donor nations and the EU.